Additional luteal support might improve IVF outcomes in patients with low progesterone level in middle luteal phase following a GnRH agonist protocol. (1st February 2021) - Tu, Jiongjiong; Lin, Ge; Gong, Fei
Abstract: Aim: The purpose of the study was to explore the efficacy of additional luteal support (ALS) for patients with low progesterone (P4) level in the middle luteal phase. Methods: A retrospective study of 1401 women who underwent their first in vitro fertilization (IVF) treatment with a GnRH agonist protocol was analyzed. Patients were divided into five groups according to P4 level in the middle luteal phase (group I>40ng/mL, group II 31–40 ng/mL, group III 21–30 ng/mL, group IV 11–20 ng/mL and group V 0–10 ng/mL. Besides routine luteal support, the group V was offered with additional oral dydrogesterone 10 mg twice daily to HCG test (ALS group). Results: After a multiple regression analysis, a similar higher hCG positive rate, clinic pregnancy rate and lower early pregnancy loss rate were achieved in group I and group V. In contrast to group I, group IV demonstrated significant lower HCG positive rate (OR = 0.65 [0.43; 0.99], p = .05), lower clinic pregnancy rate (OR = 0.60 [0.41; 0.88], p < .01) and significant higher early pregnancy loss rate (OR = 1.80 [1.08; 2.99], p = .02). The group III also resulted in significant lower clinic pregnancy rate (OR = 0.56 [0.36; 0.87], p = .01). The live birth rate tended to be higher in group I and group V but without a significant difference. Conclusion: Following agonist protocol, additional luteal support might improve IVF outcomes in patients with low serum P4 level in the middle luteal phase.